Analisis Faktor-Faktor Yang Mempengaruhi Word Of Mouth Terhadap Loyalitas Pelanggan Dr. Sophia House Of Beauty Banjarmasin - Kharisma, Gusti Dilla; , Prof. DR. H. M. Wahyuddin; , Dr. Anton Agus Setyawan, M.Si (2017)
The purpose of this research is to analyze the influence of service quality, customer satisfaction, tie strength and word of mouth on customers' loyalty. Data was collected from 130 respondents who are customers' beauty clinic of dr. Sophia house of beauty Banjarmasin. The analytical method used is path analysis. The test results concluded that all variables instruments valid and reliable as a means of collecting data. Data analysis showed that: 1) the quality of service is not positive and not significant to the word of mouth 2) customer satisfaction is significant and positive effect on word of mouth. 3) Tie strength is not positive and not significant to the word of mouth. 4) word of mouth positive and significant impact on customer loyalty.